Analisis pengaruh pemahaman dan kemampuan dalam literasi keuangan terhadap usaha mikro, kecil dan menengah. - Gunawan, Gunawan (Maliki Interdisciplinary Journal, 2025)
Having a good understanding of financial literacy is very important for a business actor, including those in the MSME sector. Because understanding financial literacy greatly influences the ongoing performance of a business. In this article entitled "analysis of the influence of understanding and ability in financial literacy on micro, small and medium enterprises" we will discuss the impact or influence of financial literacy on MSMEs. The methodology used in this research is a literature study or literature review in which the author first collects several research results in the form of articles or other sources. Then it is analyzed and synthesized. The results and discussion in this article show that having a good understanding of financial literacy for MSME business actors will have a positive impact on the sustainability of performance in MSME